Force Entrepreneurship in Contemporary Russia. Part 9: Latent Fragmentation of the Russian State - ВолковВадим Викторович (Journal of Economic Sociology, 2010)
In the final part the author depicts the characteristics of the latent state fragmentation, when the basic complex of organizational-technical state means still exist but the state itself does not. The author sees the state as a type of “head-covers” which is legal and public. The situation of competition of different structures for the taxpayer is under focus, where the state is not the only one structure. Finally the author goes to the analysis of the problem on the macro level, tackling the issues of state strengthening as they are put before Vladimir Putin.